Philosophical Approaches to Educational Assessment - Nava Nourdad (Journal of Philosophical Investigations, 2022)
During the 20th century, education assessment reflected the learners’ knowledge of the material based on their test scores. However, in recent years, with a change in societal expectations, educational expectations and practices including educational assessment have also changed. Educational philosophy has provided modified insights into the aim of education and the nature of learning. The traditional assessment of learning has been challenged and consequently complemented by the two more recent assessment philosophies of assessment for learning and assessment as learning. The resultant assessment philosophies enhance learning within their own conceptual frameworks. Reviewing the advantages and drawbacks of each educational assessment approach, the present study proposed a balanced model to achieve more comprehensive educational goals.